Sirolimus versus cyclosporine in haploidentical stem cell transplantation with posttransplant cyclophosphamide and mycophenolate mofetil as graft‐versus‐host disease prophylaxis. Issue 2 (18th March 2021) - Hernani, Rafael; Piñana, José Luis; Pérez, Ariadna; Quintero, Abdiel; Montoro, Juan; Hernández‐Boluda, Juan C.; Carretero, Carlos; Balaguer‐Roselló, Aitana; Guerreiro, Manuel; Lorenzo, Ignacio; Aguilar, Cristóbal; Giménez, Estela; et al.
Abstract: Sirolimus has emerged as an alternative to calcineurin inhibitors‐based (CNI) graft‐versus‐host disease (GVHD) prophylaxis. This retrospective study compares the outcome of 133 consecutive adult patients with haematological malignancies undergoing haploidentical stem cell transplantation with posttransplant cyclophosphamide (PTCy) and mycophenolate mofetil (MMF), combined with cyclosporine A (PTCy–CsA–MMF, n = 67) or sirolimus (PTCy–Sir–MMF, n = 66) as GVHD prophylaxis strategy. The median follow‐up was 48 (range 22–83) and 13 (range 3–33) months, respectively. PTCy–CsA–MMF was associated in multivariate analyses with a higher risk of acute kidney injury (HR 2.1, 95% CI, 1.21–3.57, p = .008) and thrombotic microangiopathy (HR 12.5, 95% CI, 1.66–93.5, p = .014), whereas PTCy–Sir–MMF was associated with a higher risk of hepatic sinusoidal obstruction syndrome (SOS) (HR 10.8, 95% CI, 1.52–77, p = .018), especially late‐onset forms, which totally resolved and none of the patients needed discontinuation of sirolimus. Two SOS‐related deaths were detected, both in the PTCy–CsA–MMF subgroup. Both GVHD prophylaxis strategies were otherwise comparable in terms of engraftment, GVHD incidence and survival.